Crystal engineering of cadmium coordination polymers decorated with nitro-functionalized thiophene-2, 5-dicarboxylate and structurally related bis(imidazole) ligands with varying flexibility1. Issue 33 (7th September 2015) - Xue, Li-Ping; Li, Zhao-Hao; Ma, Lu-Fang; Wang, Li-Ya
<x xml:space="preserve">Abstract</x> Five bis(imidazole) ligand modulated cadmium coordination polymers based on a new nitro-functionalized thiophene-2, 5-dicarboxylate ligand or 4-nitro-thiophene-2-carboxylic acid involving in situ ligand synthesis.